Critical review about two myths in fixed dental prostheses: Full-Coverage vs. Resin-Bonded, non-Cantilever vs. Cantilever. (November 2021) - Mine, Atsushi; Fujisawa, Masanori; Miura, Shoko; Yumitate, Masahiro; Ban, Shintaro; Yamanaka, Azusa; Ishida, Masaya; Takebe, Jun; Yatani, Hirofumi
Abstract: The purpose of this review was to assess the literature regarding four types of fixed dental prostheses (FDPs)/resin-bonded FDPs (RBFDPs) to provide clinicians with a comparative overview of two myths: "RBFDPs are easy to debond in patients' mouths" and "cantilever RBFDPs still have some clinical problems, especially in terms of overloading the abutment teeth and being easy to debond". A total of 782 papers were identified, 753 of which were judged unsuitable and thus excluded, leaving a total of 29 articles for inclusion in this review. The results indicated that 1) Two-retainer RBFDPs achieve clinical results comparable to full-coverage three-unit FDPs; 2) Cantilever RBFDPs show excellent long-term clinical outcomes (especially in incisor teeth) compared with other FDPs; 3) RBFDPs typically show less catastrophic failure than conventional FDPs, rebonding should be considered when debonding occurs; and 4) Cantilever RBFDPs can be recommended as defect replacement prostheses for maxillary lateral incisors and mandibular incisor teeth. Scientific field: Prosthodontics, Adhesive dentistry, Esthetic dentistry